2009
DOI: 10.1002/cncr.24568
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiocidin in sarcomas

Abstract: We investigated growth kinetics of microalgae, Chlorella vulgaris, in immobilized arrays of nanoliter‐scale microfluidic drops. These static drop arrays enabled simultaneous monitoring of growth of single as well as multiple cells encapsulated in individual droplets. To monitor the growth, individual drop volumes were kept nearly intact for more than a month by controlling the permeation of water in and out of the microfluidic device. The kinetic growth parameters were quantified by counting the increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recent studies have reported that S5a/angiocidin inhibits endothelial cell proliferation and induces endothelial cell apoptosis and antitumor activities that are related to the activity of polyubiquitin conjugates (Saeki and Tanaka, 2008). Restructuring angiocidin offers a variety of mechanisms for antitumor activity in vitro and in vivo (Sabherwal et al, 2007;L'Heureux et al, 2010;Liebig et al, 2009;Kremlev et al, 2008;Yang et al, 2006). In this study, we focused on another aspect of the antitumor activity of S5a, by inducing the differentiation of THP-1 cells into macrophages.…”
Section: Endogenous S5a Is a Crucial Protein For Monocyte Self-regulamentioning
confidence: 99%
“…Recent studies have reported that S5a/angiocidin inhibits endothelial cell proliferation and induces endothelial cell apoptosis and antitumor activities that are related to the activity of polyubiquitin conjugates (Saeki and Tanaka, 2008). Restructuring angiocidin offers a variety of mechanisms for antitumor activity in vitro and in vivo (Sabherwal et al, 2007;L'Heureux et al, 2010;Liebig et al, 2009;Kremlev et al, 2008;Yang et al, 2006). In this study, we focused on another aspect of the antitumor activity of S5a, by inducing the differentiation of THP-1 cells into macrophages.…”
Section: Endogenous S5a Is a Crucial Protein For Monocyte Self-regulamentioning
confidence: 99%
“…Colon cancer cells expressing low-level angiocidin exhibited very low proliferation rates than high expression cells. In vivo, nude mice injected with low angiocidin expression colon cancer cells develop significantly smaller tumors than the mice injected with normal cells [8][9][10][11][12] . These above results suggest that angiocidin may play a key role in tumor growth.…”
Section: Introductionmentioning
confidence: 99%